Financial Markets and Inflation Under Imperfect Information - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 1994)
This paper studies the effect of inflation on the operation of financial markets, and shows how the ability of financial intermediaries to distinguish among heterogenous firms is reduced as inflation rises. This point is illustrated by presenting a simple model where inflation affects firms' productivity. In particular, productivity differentials narrow as inflation increases. This effect creates incentives for risky and less productive firms to behave as high productivity firms. At high rates of inflation this may result in financial intermediaries being unable to differentiate among customers.